Educational Transformation through Transdisciplinarity: A route towards Curriculum Innovation - Martínez Heredia, Katia (2024)
This article focuses on reflecting on how transdisciplinarity in education fosters an integrative and creative vision, where learning is not limited to the traditional boundaries of disciplines. Transdisciplinarity, by allowing dialogue between various areas of knowledge, helps students establish meaningful connections between concepts and their practical application in the real world, promoting an education focused on active and social learning. This approach also makes students protagonists of their educational process, since learning becomes a journey of self-discovery and participation, where they can see the direct impact of their knowledge on the solution of complex problems and on their personal development. Furthermore, it analyzes how curricular innovation based on transdisciplinarity facilitates adaptation to the changes and challenges of the 21st century, providing students with the necessary tools to face a globalized and diverse environment. It also examines how transdisciplinarity allows for a more holistic and creative education, where students become active agents of their learning by connecting knowledge from various disciplines.